The Effectiveness of Anti-Lead Mask Made from Water Hyacinth on Cigarette Industry Employees in Malang City - Meidy Binarrasitha Aisyi (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
This research aims to determine the effectiveness of anti-lead mask from water hyacinth on cigarette industry employees in Malang city. By applying experimental research methods carried out on 82 workers from the 'X' cigarette factory, members of the Association of Cigarette Companies (Gapero) Malang Raya divided into 2 groups (experimental control and group), it is found that the Cigarette Industry Workers are given a mask made of water hyacinth as a filter for a group that is not given special treatment. After 2 months, the blood lead levels of cigarette factory workers are measured again and found that there is an increase in the number of factory workers with tolerable lead levels from the previous 27 people (65.85%) to 38 people (92.68%), or it can be interpreted that only 3 workers (7.32%) have excess blood lead levels in the experimental group.